VoxiGrain 1 - an Adaptive Music Instrument - Sérgio Miguel Ferreira de Azevedo Coutinho (2023)
This thesis chronicles the design, development, and socio-cultural implications of VoxiGrain 1, an adaptive musical instrument engineered to cater to people with diverse abilities. Drawing on a multidisciplinary approach that melds technological innovation with social empathy, the research delves into the challenges and opportunities that arise when crafting a musical instrument for inclusive human-centered interaction. Guided by mentors, case studies, and hands-on fieldwork at the APPC (an organization for people with disabilities), the project offers both a tangible outcome in VoxiGrain 1 and a theoretical framework for rethinking accessibility in musical engagement. The work contributes to an emerging body of knowledge that aims to democratize artistic practice through technology. It highlights the critical need for an interdisciplinary dialogue, suggesting that the marriage of engineering prowess and empathetic design can yield solutions that are technologically sound and socially responsible. This research is not just a narrative of a quest to build an inclusive musical instrument but also a philosophical exploration of what it means to be truly 'adaptive' in contemporary society. VoxiGrain 1 serves as a case study, offering insights that have broader applicability for designers, artists, and social practitioners interested in creating more inclusive environments.